IMPORTANCIA DE LAS DECLARACIONES ANUALES PARA PERSONAS FÍSICAS IMPORTANCE OF ANNUAL DECLARATIONS FOR NATURAL PERSONS - Ocaña, Jesus Fernando Cárdenas (IJRDO - Journal of Business Management, 2022)
natural persons are one of the most used regimes to register a company before the SAT, only in previous years have exceeded the figure of 30 million existing natural persons, this indicates the importance of being registered in the SAT so that the companies are officially formal, because with this it indicates that they will be complying with the payment due of their taxes, taxes are a great source of income for the government because these resources are destined to the public treasury with which it is intended to help society. This research brings us a little closer to the importance of making annual declarations before the SAT for the proper fulfillment of your obligations as an entrepreneur. A descriptive method was used for the type of research it is.